Cp*Co(iii)-Catalyzed oxidative [5+2] annulation: regioselective synthesis of 2-aminobenzoxepines via C–H/O–H functionalization of 2-vinylphenols with ynamides. Issue 82 (18th September 2018) - Han, Xiang-Lei; Liu, Xu-Ge; Lin, E; Chen, Yunyun; Chen, Zhuangzhong; Wang, Honggen; Li, Qingjiang
Abstract : A Cp*Co(iii )-catalyzed [5+2] C–H annulation reaction of 2-vinylphenols with ynamides toward the regioselective synthesis of 2-aminobenzoxepines has been reported. Abstract : A Cp*Co(iii )-catalyzed [5+2] C–H annulation reaction of 2-vinylphenols with ynamides was developed. The reaction led to the efficient synthesis of valuable 2-aminobenzoxepines in high regioselectivity. Mild reaction conditions, good functional group tolerance, and moderate to good yields were observed. The synthetic utility was demonstrated by a gram-scale synthesis and further transformations of the products. Preliminary mechanistic studies were conducted, and a possible catalytic cycle was proposed.